Prospective Randomized Control Trial Comparing the Efficacy of Diathermy Incision versus Scalpel Incision over Skin in Patients Undergoing Inguinal Hernia Repair - B.V. Gogeri2, A.S. Godhi2, S.C. Metgud2, Patil Shivagouda1,2* (Recent Research in Science and Technology, 2010)
Abstract Background: Electrocautery in surgery is widely used except for the skin incisions, this is because of fear of scarring of tissues, post operative pain, and wound infection in view of devitalisation of tissues. This study compares the scalpel incisions with electrocautery incision over skin in patients undergoing hernia repair. Materials and Methods: In this study prospective randomized study 60 patients undergoing mesh repair for inguinal hernia are divided in to two groups. In Group A skin incision is taken with electrocautery , and in Group B incision is taken with scalpel. Postoperative pain, wound complication and requirement of analgesic are compared between the two groups. Results: The two groups did not differ in relation to post operative pain. Post operative analgesic requirement are similar in two groups and post operative complications seroma, hematoma, purulent collection are comparable in two groups. Conclusion: Although results are comparable in two groups, electrocautery can be safely used in making skin incisions as results are comparable in two groups .We recommend further broad study of electrocautery usage in other surgical procedure and its further evaluation. Keywords: Electrocautery, Scalpel, Skin incision